Linguistic ambiguity of modification - SALEH , YASIR MOHAMMED; HASAN , SAIF HABEEB; HAMEED, ALI MUSAAB (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT This paper explains the ambiguity in using modifiers and shows its types. The research contains an analysis of some ambiguous sentences with an explanation of the reasons behind this ambiguity. It presents a theoretical background about modification in general and clarifies different types of ambiguity. It depends on the available grammar sources and the internet to provide enough material. It shows that a modifier is an optional element that depends on the headword. There are two types of modification, also, there are two types of ambiguity. Phrasal verbs can be interpreted in more than one way. RESUMEN Este artículo explica la ambigüedad en el uso de modificadores y muestra sus tipos. La investigación contiene un análisis de algunas frases ambiguas con la explicación de las razones detrás de esta ambigüedad. Presenta un trasfondo teórico sobre la modificación en general y aclara diferentes tipos de ambigüedad. Depende de las fuentes gramaticales disponibles e Internet para proporcionar suficiente material. Muestra que un modificador es un elemento opcional que depende del encabezado. Hay dos tipos de modificaciones, además, hay dos tipos de ambigüedad. Los phrasal verbs se pueden interpretar de más de una forma.